2009
DOI: 10.1111/j.1476-5381.2009.00206.x
|View full text |Cite
|
Sign up to set email alerts
|

Current status and challenges of cytokine pharmacology

Abstract: The major concern of pharmacology about cytokines has originated from plentiful data showing association between gross changes in their production and pathophysiological processes. Despite the enigmatic role of cytokines in diseases, a number of them have become a subject of cytokine and anti-cytokine immunotherapies. Production of cytokines can be influenced by many endogenous and exogenous stimuli including drugs. Cells of the immune system, such as macrophages and lymphocytes, are richly endowed with recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 302 publications
(224 reference statements)
0
57
0
Order By: Relevance
“…IL-10, IL-11, anti-IL-12, anti-TNF-α are used for the prevention of psoriasis. Cytokines which are antiinflammatory in nature, like IL-10 and IL-11, are used in Crohn's disease and ulcerative colitis [2]. Treatment with altrakincept, a recombinant human soluble IL-4 receptor, neutralizes endogenously produced IL-4 in bronchial asthma patients [43].…”
Section: Cytokines As Therapeutic Targetsmentioning
confidence: 99%
See 2 more Smart Citations
“…IL-10, IL-11, anti-IL-12, anti-TNF-α are used for the prevention of psoriasis. Cytokines which are antiinflammatory in nature, like IL-10 and IL-11, are used in Crohn's disease and ulcerative colitis [2]. Treatment with altrakincept, a recombinant human soluble IL-4 receptor, neutralizes endogenously produced IL-4 in bronchial asthma patients [43].…”
Section: Cytokines As Therapeutic Targetsmentioning
confidence: 99%
“…Disease Targets IFN-α Hepatitis B and C [5] IFN-β Multiple sclerosis [5] IFN-γ Chronic granulomatous disease [38], Crohn's disease [65], Multidrug resistant tuberculosis [42] TNF-α Rheumatoid arthritis [30,31], Sepsis [32], Refractory asthma [33], Psoriasis [2] G-CSF Idiopathic neutropenia, Congenital neutropenia, Febrile neutropenia, Leukemic neutropenia, Aplastic neutropenia [37], Bone marrow suppression [5] GM-CSF Bone marrow suppression, Crohn's disease [5] IL-2 Metastatic melanoma, Renal cell carcinoma [46] IL-4 Asthma [43] IL-5 Asthma [44] IL-6 Rheumatic diseases [34] IL-10 Crohn's disease, Ulcerative colitis [2], Psoriasis, Rheumatoid arthritis [5] IL-11 Crohn's disease, Ulcerative colitis, Psoriasis, Rheumatoid arthritis [2] IL-13 Asthma [2,45] Erythropoietin Anaemia, Bone marrow failure [5] HER2-Specific Monoclonal Antibody Adenocarcinoma of stomach, Breast cancer [35,36] …”
Section: Cytokinesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, its relationship with some pro-inflammatory cytokines is important for the outcome of infection and sepsis. 48 In the present study, the first cytokine that began to rise in the liver of the infected mice was IL-10. C. coli 26536 induced the strongest anti-inflammatory IL-10 response in the liver by the last day of infection (day 8).…”
Section: Discussionmentioning
confidence: 99%
“…43 Furthermore, the immune functions of cytokines result from the coordinated action of T cells, macrophages and dendritic cells, and these largely depend on the recruitment of these calls to the sites of infection and inflammation, and to other pathological lesions. 48 Previously, Hu et al (2006) 49 demonstrated that C. jejuni infection can trigger innate inflammatory responses, and induce human dendritic cell maturation and production of pro-inflammatory cytokines, including IL-6, IL-8, IL-12 and TNF-a. In this way, cytokines can induce Campylobacter-specific Th1 effector-cell responses, and contribute to the pathogenesis and clinical symptoms of Campylobacter spp.…”
Section: Discussionmentioning
confidence: 99%